1987
DOI: 10.1172/jci112926
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of postprandial lipoprotein metabolism in normal, type IIa, type III, and type IV hyperlipoproteinemic individuals. Effects of treatment with cholestyramine and gemfibrozil.

Abstract: To study exogenous fat metabolism, we used the vitamin A-fat loading test, which specifically labels intestinally derived lipoproteins with retinyl palmitate (RP). Postprandial RP concentrations were followed in total plasma, and chylomicron (Sf > 1,000) and honchylomicron (Sf < 1,000) fractions. In normal subjects postprandial lipoproteins were present for more than 14 h, and chylomicron levels correlated inversely with lipoprotein lipase activity and fasting high density lipoprotein (HDL) cholesterol levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
141
5
5

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(171 citation statements)
references
References 55 publications
20
141
5
5
Order By: Relevance
“…A positive correlation between fasting plasma triglyceride concentrations and postprandial lipemia has been found in several previous studies, 17 and Weintraub et al 18 reported greatly elevated postprandial lipemia in men with fasting triglyceride concentrations between 315 and 2,758 mg • dl" 1 (mean, 808±679 mg • dr 1 )-In the present study, the hypertriglyceridemic group was limited to individuals with apparently mild defects in triglyceride metabolism. In this group postprandial plasma triglyceride excursions were highly heterogeneous, and in some individuals the magnitude of postprandial lipemia was clearly well within the normal range.…”
Section: Discussionsupporting
confidence: 80%
“…A positive correlation between fasting plasma triglyceride concentrations and postprandial lipemia has been found in several previous studies, 17 and Weintraub et al 18 reported greatly elevated postprandial lipemia in men with fasting triglyceride concentrations between 315 and 2,758 mg • dl" 1 (mean, 808±679 mg • dr 1 )-In the present study, the hypertriglyceridemic group was limited to individuals with apparently mild defects in triglyceride metabolism. In this group postprandial plasma triglyceride excursions were highly heterogeneous, and in some individuals the magnitude of postprandial lipemia was clearly well within the normal range.…”
Section: Discussionsupporting
confidence: 80%
“…The classical and widely used way is to add retinol (vitamin A) into the test meal (20-50 000 IU) and to assay retinol palmitate in total plasma (or separately TRL and non-TRL fractions) (Weintraub et al, 1987(Weintraub et al, , 1988Cohn et al, 1993;Karpe et al, 1995;Guerci et al, 2001). Indeed, retinol palmitate is specifically accumulated and secreted into native chylomicrons and minor exchanges with other kinds of lipoproteins are thought to occur.…”
Section: Chylomicrons Remnantsmentioning
confidence: 99%
“…Because all classes of lipoproteins are interrelated, every kind of lipoprotein can be altered postprandially (Patsch et al, 1983;Weintraub et al, 1987;Cohn et al, 1988a, b;Karpe et al, 1993Karpe et al, , 1995Dubois et al, 1994Dubois et al, , 1998. If the full pattern of lipoprotein parameters, including LDL and HDL particles, is required, these can be separated from plasma samples by a more prolonged ultracentrifugation and components assayed (triglycerides, cholesterol and phospholipidsapolipoproteins).…”
Section: Ldl and Hdlmentioning
confidence: 99%
“…Estimates of the interindividual variability (SDs) of triglycerides and vitamin A responses, namely AUC, were expressed in brackets as CV%. The 0±7 h area under the curves (AUCs) were calculated by the trapezoidal method (Dubois et al, 1994;Weintraub et al, 1987). The statistical signi®cance (P`0.05) of the differences found, between the four test meals (individual time-points of AUCs) or between the 0±7 h time points values for a given test-meal, were assessed by using analysis of variance (ANOVA) for paired values (Winner, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…The Sf b1000 fraction containing CMs plus large CM-remnants (CMRs) was isolated as usually done from a 2 mL serum layered under 3 mL 0.9% NaCl by ultracentrifugation at 10 C (24 000 6 g for 1 h, 1.6 6 10 6 6 g min) in a Beckman (Palo Alto, CA) 40.3 rotor (Dubois et al, 1994;Weintraub et al, 1987). Note that the Svedberg¯otation unit (Sf) is expressed in Svedberg (S) 6 10 713 s and that a Sf b1000 value correspond to particles of d`0.96 g/mL, namely CMs and their large CMRs.…”
Section: Analytical Determinationsmentioning
confidence: 99%